Endodontic Prognosis Clinical Guide for Optimal Treatment Outcome - Chugal, Nadia; Lin, Louis M.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book serves as a clinical guide to help the practitioner improve endodontic treatment outcomes. It focuses on the various factors affecting the prognosis of endodontic treatments and on their impact on short-term and long-term results. The text incorporates up-to-date knowledge, techniques and treatment protocols. Each chapter has been carefully chosen to address either foundational knowledge or a select aspect of endodontic treatment. The authors analyze the knowledge accumulated from a large number of outcome studies and provide the reader with a critical appraisal indicating the strengths and weaknesses of those studies. This information is then used to make recommendations on how to predict the outcome of the intended treatment. The authors emphasize that the endodontic prognosis is a multifactorial phenomenon, underscoring how various factors, singularly and in combination, influence the treatment outcome. Readers are provided with tools to successfully assess the prognosis of the proposed treatment at the outset and to execute the planned treatment focused on optimal outcome.
INTRODUCTION: Fundamentals of Endodontic Prognosis -- Natural History and Expected Outcome of Endodontically Treated Tooth. CONSIDERATIONS FOR TREATMENT PLANNING: Microbiology and Immunology of Endodontic Infection -- Endodontic Radiography -- Endodontic Diagnosis of Pulpal and Periradicular Disease -- Endodontic Treatment of Mature Teeth -- Endodontic Treatment of Immature Teeth with Open Apex -- Pharmacotherapeutics and Peri- and Postoperative Pain Management -- Systemic and Genetic Considerations for Endodontic Treatment. TREATMENT PROCEDURES AND THEIR EFFECT ON OUTCOME: Anatomy, Access and Length Determination -- Instrumentation and Disinfection of Root Canals -- Obturation of Root Canals -- Restoration of Endodontically Treated Teeth -- Local Risk Factors in Relation to Endodontic Treatment Outcome. FOLLOW UP AND OUTCOME ASSESSMENT: Criteria for Outcome Assessment -- Tooth Retention vs Extraction and Alternatives.
Keywords: Dentistry; Dentistry; Dentistry